Exploring Occupational Therapy in the Punk Community: A Qualitative-Ethnographic Study - Ana Syifa’u Nafilah; Lis Sarwi Hastuti; Erayanti Saloko (Poltekkes Kemenkes Surakarta, 2024)
Background: The punk community is a subculture that is often viewed as contrary to the dominant culture. Society often misunderstands this community, constructing it as a negative and marginalized group. Occupational therapy strives to be more diverse, fair, and inclusive in order to strengthen practitioners' contributions to healthy and engaged communities. This study aims to explore the forms and meanings of occupation in the punk community through an occupational perspective. Methods: This study uses qualitative methods with an ethnographic approach. Respondents were selected through purposive sampling and snowball sampling techniques. Data collection was conducted through semi-structured in-depth interviews, observation, and documentation. Data analysis used ethnographic thematic methods, while data validity was tested through source triangulation. Results: Thematic ethnographic analysis produced two main themes related to the exploration of occupation in the punk community. The first theme concerns the forms of occupation in the punk community, which include anti-mainstream, egalitarian, and DIY (Do-It-Yourself) aspects. The second theme discusses the meaning of occupation in the punk community, which includes working as a means of survival, occupation as self-expression, occupation as a form of contribution and concern for others, and participation in occupation to improve welfare and a sense of belonging. Conclusion: The forms and meanings of occupation in the punk community are very different from those in society at large. The beliefs and environment of the punk community shape unique occupational choices compared to the wider community. The results of this study emphasize the importance of expanding the scope of occupational therapy practices to be more inclusive.